Quantum Multiagent Actor-Critic Neural Networks for Internet-Connected Multirobot Coordination in Smart Factory Management - Yun, Won Joon; Kim, Jae Pyoung; Jung, Soyi; Kim, Jae Hyun; Kim, Joongheon (IEEE Internet of Things Journal, 2023)
As one of the latest fields of interest in both academia and industry, quantum computing has garnered significant attention. Among various topics in quantum computing, variational quantum circuits (VQCs) have been noticed for their ability to carry out quantum deep reinforcement learning (QRL). This article verifies the potential of QRL, which will be further realized by implementing quantum multiagent reinforcement learning (QMARL) from QRL, especially for Internet-connected autonomous multirobot control and coordination in smart factory applications. However, the extension is not straightforward due to the nonstationarity of classical MARL. To cope with this, the centralized training and decentralized execution (CTDE) QMARL framework is proposed under the Internet connection. A smart factory environment with the Internet of Things (IoT)-based multiple agents is used to show the efficacy of the proposed algorithm. The simulation corroborates that the proposed QMARL-based autonomous multirobot control and coordination performs better than the other frameworks.
Keywords: C. thin film transistor (TFT); Computational modelling; Encodings; Multi-agent reinforcement learning; Quantum Computing; Quantum deep learning; Robots control; Smart factory; Smart manufacturing; Multiagent reinforcement learning (MARL); quantum computing; quantum deep learning (QDL); robot control; smart factory